استخدام رشاحة بعض الفطريات كعوامل مكافحة حيوية وsodium benzoate وpotassium sorbate في حماية نبات الفليفلة من الفطرين الممرضين Fusarium oxysporum و F.solani (Latakia University Journal -Biological Sciences Series, 2017)
ثبطت رشاحة الفطور المستخدمة في التضاد الحيوي مثل Trichoderma harzianum،T.viride ، Aspergillus niger، Saccharomyces cerevisiae والمستحضر التجاري (بيوكنت) الحاوي على T.harzianum النمو الإعاشي للفطر الممرضF.solani بنسبة تثبيط وصلت إلى 75%، 68 % ،50%،30.7 ،61.5%على التوالي، وللفطرF.oxysporum بنسبة تثبيط وصلت إلى83.5 % ،75.5% ،38.8 %،22,2 % و68.8%على التوالي مقارنة بالشاهد. تفوقت رشاحة الفطر T.viride بتأثيرها في الوزن الجاف للفطريين الممرضين F.oxysporum و F.solani حيث وصلت نسبة التثبيط إلى 83.5% و84.5% على التوالي عند التركيز%20. أظهرت النتائج انخفاضاً في الوزن الجاف للفطريين الممرضين مع ازدياد تركيز سوربات البوتاسيوم وبنزوات الصوديوم حيث وصلت نسبة التثبيط مقارنة مع الشاهد في حالة بنزوات الصوديوم إلى 63%و76%و96% و100%و سوربات البوتاسيوم الى80% و86.5% و91% و100% عند التراكيز 0.2 و0.4 و0.6 و0.8 ملغ /مل على التوالي. ساهم نقع بذور الفليفلة لمدة 12 ساعة بخليط من رشاحة الفطور المستخدمة في التضاد الحيوي بتركيز20% كل على حده مع محلول سوربات البوتاسيوم وبنزوات الصوديوم بتركيز0.4 ملغ/مل في زيادة نسبة الإنبات من48% في معاملة الشاهد إلى 95 % و91% و73% و63% و89% على التوالي عند زراعتها في تربة ملوثة بالفطر F.oxysporum في حين أن المعاملة لـ 6 ساعات رفع النسبة المئوية للإنبات في تربة ملوثة بالفطر الممرض F.solani إلى85 %و87% و69% و65% و83%. Anti-fungal Tichoderma harzianum, T.viride, Aspergillus niger, Saccharomyces cerevisiae and the commercial preparation (Biocont) inhibited the filamentous growth of the pathogenic fungi Fusarium solani by 75% , 68% , 50%, 30,7% and 61,5% respectively, and for F. oxysporum by 83,2% , 75,5% ,38,8% , 68,8% and 76% respectively compared with the control. T.viride at concentration filtrate (20%) surpassed the dry weight of both pathogenic fungi (F. oxysporum and F. solani) by 83.5% and 84.5% respectively.The results showed a decline in the dry weight of both pathogenic fungi with increased concentration of potassium sorbate and sodium benzoate, reaching inhibition ratio to 63% , 76%, 96% and 100% compared with the control in the case of sodium benzoate, and 80% ,86.5%, 91% and 100% in the case of potassium sorbate when using concentrations of 0.2, 0.4, 0.6 and 0.8 mg / ml respectively.Soaking the pepper seeds for 12 hours with a mixture of 20% anti-fungal filtrate separately with 0.4 mg/ml potassium sorbate and sodium benzoate solution contributed in the increasing of germination rate from 48% in the control to 95% , 91% , 73% ,63%and 89% on respectively. when grown in contaminated soil fungus F.oxysporum while the treatment for 6 hours to raise the percentage of germination in contaminated soil fungus pathogen F.solani to 85% and 87% and 69% and 65% and 83%.